THE INTERPRETATION OF THE FIRST VERSE [KETUHANAN YANG MAHA ESA] OF PANCASILA - Saiful Hakam (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2017)
Historically, In Indonesia, there are two interpretation of the first verse of Pancasila. The first is [Pengakuan adanya Tuhan] Recognition of the Divine Omnipotence. This translation is used to use by secular group including communist and non-Muslim group especially Buddhist and Hindus. This interpretation was dominant in 1945-1965 when Sukarno as the creator of Pancasila still dominated the political power. Or, this verse was dominant when the secular-nationalist group still had strong position in Indonesia. The fact of it is during the time there was no a policy about official religions from state and the requirement of religious teaching in schools and universities. And, it must be noted that Sukarno as the creator of Pancasila in Guided Democracy era, strongly interpreted Pancasila in his speech and address as the Nasakom that is National, Religion, and Communist. Sukarno as the creator of Pancasila strongly insisted that he was truly nationalist and in his heart he was a truly Muslim. So, it can be said the Recognition of the Divine Omnipotence is the original interpretation of the first verse of Pancasila. My argumentation is originally in the early beginning of the Republic the meaning of religion was religion as a faith not as an institution